What can exome sequencing do for you?. Issue 9 (5th July 2011) - Majewski, Jacek; Schwartzentruber, Jeremy; Lalonde, Emilie; Montpetit, Alexandre; Jabado, Nada
Abstract : Recent advances in next-generation sequencing technologies have brought a paradigm shift in how medical researchers investigate both rare and common human disorders. The ability cost-effectively to generate genome-wide sequencing data with deep coverage in a short time frame is replacing approaches that focus on specific regions for gene discovery and clinical testing. While whole genome sequencing remains prohibitively expensive for most applications, exome sequencing—a technique which focuses on only the protein-coding portion of the genome—places many advantages of the emerging technologies into researchers' hands. Recent successes using this technology have uncovered genetic defects with a limited number of probands regardless of shared genetic heritage, and are changing our approach to Mendelian disorders where soon all causative variants, genes and their relation to phenotype will be uncovered. The expectation is that, in the very near future, this technology will enable us to identify all the variants in an individual's personal genome and, in particular, clinically relevant alleles. Beyond this, whole genome sequencing is also expected to bring a major shift in clinical practice in terms of diagnosis and understanding of diseases, ultimately enabling personalised medicine based on one's genome. This paper provides an overview of the current and future use of next generation sequencing as it relates to whole exome sequencing in human disease by focusing on the technical capabilities, limitations and ethical issues associated with this technology in the field of genetics and human disease.